2021
DOI: 10.1063/5.0035038
|View full text |Cite
|
Sign up to set email alerts
|

Void engineering in epitaxially regrown GaAs-based photonic crystal surface emitting lasers by grating profile design

Abstract: We report the engineering of air voids embedded in GaAs-based photonic crystal surface-emitting lasers realized by metalorganic vapor-phase epitaxy regrowth. Two distinct void geometries are obtained by modifying the photonic crystal grating profile within the reactor prior to regrowth. The mechanism of void formation is inferred from scanning transmission electron microscopy analysis, with the evolution of the growth front illustrated though the use of an AlAs/GaAs superlattice structure. Competition between … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…For samples A and C, even the etching depth varied a lot, the upper parts of the air-hole shape were very similar, and the height of the dome top of air voids was nearly identical. The geometries indicated that the coalesce of the air voids is determined by the lateral growth through the (100) plane on the plateau of the PC region, the growth through the {100} plane of the side wall, and through the higher index plane indicated by the yellow dashed line . The initial high growth rate was intended to enhance the growth along the [001] direction over the lateral growth to retain the air voids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For samples A and C, even the etching depth varied a lot, the upper parts of the air-hole shape were very similar, and the height of the dome top of air voids was nearly identical. The geometries indicated that the coalesce of the air voids is determined by the lateral growth through the (100) plane on the plateau of the PC region, the growth through the {100} plane of the side wall, and through the higher index plane indicated by the yellow dashed line . The initial high growth rate was intended to enhance the growth along the [001] direction over the lateral growth to retain the air voids.…”
Section: Resultsmentioning
confidence: 99%
“…The geometries indicated that the coalesce of the air voids is determined by the lateral growth through the (100) plane on the plateau of the PC region, the growth through the {100} plane of the side wall, and through the higher index plane indicated by the yellow dashed line. 25 The initial high growth rate was intended to enhance the growth along the [001] direction over the lateral growth to retain the air voids. Sample B was grown using a thicker faster growth stage than the other two samples; however, the variation of the geometry of the air voids is not obvious.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Historically PCSELs have been formed by wafer fusion, but these devices suffered from low output powers due to defect states in the PC region as a result of regions of discontinuous crystallinity formed during the wafer fusion process 7 9 . More recently our group 10 12 along with several others have demonstrated PCSELs formed by epitaxial regrowth 13 17 . The move to epitaxial regrowth by metalorganic vapour phase epitaxy (MOVPE) has demonstrated a pathway to high volume production of highly reliable devices leveraging all the knowledge gained over many years of InP DFB development.…”
Section: Introductionmentioning
confidence: 89%
“…Thin layer of AlGaAsSb material covers etched GaSb surface even inside of the etched holes. However, the self-shadowing of the etched holes from atomic fluxes incoming at the angle to surface normal and tendency of (100) surfaces to promote lateral growth due to higher adatom surface mobility (compared to high index surfaces) [8] leads to merging of the growth fronts and formation of the buried voids. As a result, air-pockets were encapsulated within ~500 nm of the p-cladding material.…”
Section: Gasb-based Pcsel Fabricationmentioning
confidence: 99%